Set of 15 SNP-SNP Markers for Detection of Unbalanced Degraded DNA Mixtures and Noninvasive Prenatal Paternity Testing - Zhang, Ranran; Tan, Yu; Wang, Li; Jian, Hui; Zhu, Jing; Xiao, Yuanyuan; Tan, Mengyu; Xue, Jiaming; Yang, Fan; Liang, Weibo (Frontiers in Genetics, 2022)
Unbalanced and degraded mixtures (UDM) are very common in forensic DNA analysis. For example, DNA signals from criminal suspects are masked by a large amount of DNA from victims, or cell-free fetal DNA (cffDNA) in maternal plasma is masked by a high background of maternal DNA. Currently, detecting minor DNA in these mixtures is complex and challenging. We developed a new set of SNP-SNP microhaplotypes with short amplicons, and successfully genotyped them using the new method of amplification-refractory mutation system PCR (ARMS-PCR) combined with SNaPshot technology based on a capillary electrophoresis (CE) platform. This panel reflects a high polymorphism in the Southwest Chinese Han population and thus has excellent potential for mixture studies. We evaluated the feasibility of this panel for UDM detection and noninvasive prenatal paternity testing (NIPPT). 15 SNP-SNPs detected minor DNA of homemade DNA mixtures, with a sensitivity of 0.025-0.05 ng, and a specificity of 1:1000. In addition, the panel successfully genotyped degraded DNA from single and mixed samples. Finally, 15 SNP-SNPs were applied to 26 trios. All samples displayed positive results with at least one marker to detect cffDNA. Besides, all fetal alleles in maternal plasma were confirmed by genotyping fetal genomic DNA from amniocentesis and paternal genomic DNA from peripheral blood. The results indicated that the SNP-SNP strategy based on the CE platform was useful for UDM detection and NIPPT.